Measurement of day and night neutrino energy spectra at SNO and constraints on neutrino mixing parameters. - Ahmad, Q; Allen, R; Andersen, T; Anglin, J; Barton, J; Beier, E; Bercovitch, M; Bigu, J; Biller, S; Black, R; Blevis, I; Boardman, R; et al. (2002)
The Sudbury Neutrino Observatory (SNO) has measured day and night solar neutrino energy spectra and rates. For charged current events, assuming an undistorted 8B spectrum, the night minus day rate is 14.0%+/-6.3%(+1.5%)(-1.4%) of the average rate. If the total flux of active neutrinos is additionally constrained to have no asymmetry, the nu(e) asymmetry is found to be 7.0%+/-4.9%(+1.3%)(-1.2%). A global solar neutrino analysis in terms of matter-enhanced oscillations of two active flavors strongly favors the large mixing angle solution.